Workshop And Training Of The Drug-Drug Interaction Database Using Indonesian Drug Brand Names - Arli Aditya Parikesit; David Agustriawan; Margareta Deidre Valeska; Andreas Whisnu; Moch Firmansyah; Ike Veneqe; Audrey Amira Crystalia (STMIK Royal, 2022)
Indonesia International Institute for Life Sciences (i3L) and Lira Medika Hospital have developed a customized drug-drug interaction database, named as DDIBase. It has a comprehensive library for providing annotation-specific information toward the drug targets, mechanism, and interaction with other drugs. Hence, DDIBase is a new database with a brand-new user interface as well. In this regard, as DDIBase has currently reached beta stage of development, it is required to provide more comprehensive user feedback to improve its features. Thus, a workshop has been devised to explain the user guidelines, while a training has been conducted to provide system demo and user hand-on. The workshop and training attendees are faculty members of the i3L and Lira Medika Hospital Staffs. A survey has been developed to cater the user satisfaction toward the DDIBase. In this end, the survey has elicited good user satisfaction toward the developed user interface.